2019
DOI: 10.1177/1352458519876032
|View full text |Cite
|
Sign up to set email alerts
|

Brain anatomical correlates of fatigue in multiple sclerosis

Abstract: Fatigue is one of the most debilitating symptoms in patients with multiple sclerosis (MS). Despite its clinical significance, the aetiology and pathophysiology of MS-related fatigue are not well understood. Current evidence and understanding of the neuroanatomical underpinnings of MS-related fatigue are reviewed in this article. The aims of this paper are to (1) review the findings of previous structural neuroimaging studies on MS-related fatigue and summarize consistent findings regarding brain circuitry asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 92 publications
0
41
1
Order By: Relevance
“…Medication was defined as a dichotomous variable, based on treatment with at least one of the above-mentioned medications. Since depression is a significant confounder of fatigue, 2 we ran a third GLM analysis adjusting also for CES-D (in addition to age, sex, disease duration, EDSS, and medication).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medication was defined as a dichotomous variable, based on treatment with at least one of the above-mentioned medications. Since depression is a significant confounder of fatigue, 2 we ran a third GLM analysis adjusting also for CES-D (in addition to age, sex, disease duration, EDSS, and medication).…”
Section: Methodsmentioning
confidence: 99%
“…1 The neural basis of fatigue has been investigated in several magnetic resonance imaging (MRI) studies. 2 These studies showed associations between fatigue and structural brain abnormalities that characterize MS, such as white matter lesions 36 and brain atrophy. 4,79 However, among the plethora of neuroimaging studies investigating the relationship between those structural brain abnormalities and fatigue, only some showed significant associations, while others failed to replicate those findings.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,14 Interestingly, MS patients show impaired reward responsiveness, especially when suffering from fatigue. 15 Moreover, neuroimaging studies have shown overlapping structural and functional alterations of mesocorticolimbic pathways in MS patients Fatigue, depression, and pain in multiple sclerosis: How neuroinflammation translates into dysfunctional reward processing and anhedonic symptoms suffering from fatigue, 1,16 depression, 2,4 and pain. 17 Furthermore, all three symptoms have been linked to dysfunction of monoaminergic neurotransmission in central nervous system (CNS) inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we will discuss the potential therapeutic implications and limitations of such a framework. 11,18,19,21,22 Neuroimaging findings Fatigue, depression, and pain are associated with several structural and functional changes of the brain in MS 1,2,4,16,17 and beyond. 1,23,24 Such changes have been most consistently observed in the prefrontal cortex, the basal ganglia, and the limbic system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation